Study the Prevalence of Pigeon Coccidiosis in Baghdad City: Elaph F. Mahdii and Haidar M. A. Al-Rubaie - Mahdii, Elaph F. (The Iraqi Journal of Veterinary Medicine, 2013)
The present study was conducted to record the prevalence of pigeon coccidiosis in Baghdad city. Out of 40 birds 14 (35%) were infected with Eimeria spp. which divided into 8 males (38.09 %) and 6 females (31.57 %). Insignificant effects on the body weight gain was recorded between the infected birds (234.78 ± 6.32g ) and non infected once ( 258.461 ± 9.2g ) ; Also in both sex males (236.87 ± 9.41g , 260.07 ± 10.88g ) and females ( 232 ± 8.63g , 256.84 ± 15.29g ) respectivel